European Identity Today: Thought or Feeling? - A. Yu. Kolianov (Дискурс)
Introduction. The paper analyzes the strategies for the formation of European identity.  The author examines how identity was conceptualized in political science through the history of the development of the concepts of nation and community. The constructivist interpretation of the nation as an “imaginary community” and the understanding of identity as a direct holistic understanding of oneself as a unique unit of the national political culture in relation to the rest of the world today form the basis of the political direction of European integration.Methodology and sources. In conducting the study, a comparative historical method, an analysis of sources (official documents, scientific and journalistic texts), a discourse analysis, and also data from opinion polls were used.Results and discussion. Political crises of the last two decades have shown that the dominant theories of European integration in the last century, focused on economic aspects, are not always able to give adequate answers to the political challenges of our time, which sometimes puts the construction of a united Europe in a precarious position. The question of what makes Europe common remains open and no less, and perhaps even more relevant than before. The political essence of united Europe remains abstract and is not fully understood by Europeans as the subjective component of an individual political culture. In this paper, an attempt is made to trace the transformation of a request for political identity. Promising for the sociocultural development of European identity and the formation of a collective sense of self is a guide to the deliberative activities of the population and elites to determine the vector of political integration.  A constructivist approach in this direction allows us to make positive forecasts for relations between the EU and Russia.Conclusion. The obviousness of the ideological request for the construction of a European identity is manifested in the nature of current scientific discourse, broadcast through the media and mass culture products, and is also formulated in the system of priorities of Europeans.  In fact, the 2010-ies became for the EU a period when the political component of integration processes began to come to the fore.